Autokreacja w statusach komunikatorów sieciowych - Jankowska, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2007)
Self-creation in the net messengers status descriptions is manifested more or less consciously through language means supported by pre-arranged graphic and iconic signs symbolizing user’s temporary moods, for example: © smile, :-D laughter, ;-) wink, :-/ disapproval, :-o surprise. By means of net messengers status descriptions users create their own image. They do it practicing various ingratiation techniques. In the material studied, vulgar language, foreign words and verbal expressions were noted. The intention of this kind of speaker’s action is the willingness to attract attention, provoke response among other users and create the image of an original, emotional, imaginative and inventive human being. The exposition of individual personality using linguistic means creates individual self-characterization, which is a trademark of the speaker.